A second chance to dream: initiating ODeL in secondary school re-entry programs for young adult secondary school dropouts the case of Mumias District, Western Kenya. Issue 1 (2nd January 2018) - Musita, Richard; Ogange, Betty O.; Lugendo, Dorine
Abstract: The Kenyan education system has very limited re-entry options for learners who drop out before attaining secondary school certificate. It is very difficult to access training and or secure a job that requires at least secondary school education. This study examined the prospects of initiating Open and Distance e-Learning(ODeL) in re-entry programmes into high school for out of school Young Adult Secondary School Dropouts (Y.A.S.S.D). The study focused on the enablers and challenges of initiating ODeL in the secondary school re-entry programmes. An alternative flexible and sustainable community based ODeL model that potentially can address re-entry for the Y.A.S.S.D is proposed. A qualitative phenomenological design was used; focus group discussion and interviews were conducted from a purposeful sample of participants. The study revealed that the potential of ODeL in addressing re-entry into secondary school for Y.A.S.S.D great. Majority of the participants were aware of the existing secondary school re-entry options, however, ODeL appeared new. Despite there being challenges in introducing the ODeL mode of study in secondary school re-entry programmes, it is viable and requires further exploration. The enablers of this mode of study are largely in place to the extent appreciated by participants in the study.